SUMOylation and NEDDylation in Primary and Metastatic Cancers to Bone - Gomarasca, Marta; Lombardi, Giovanni; Maroni, Paola (Frontiers in Cell and Developmental Biology, 2022)
Post-translational modifications comprise series of enzymatically-driven chemical modifications, virtually involving the entire cell proteome, that affect the fate of a target protein and, in turn, cell activity. Different classes of modifications can be established ranging from phosphorylation, glycosylation, ubiquitination, acetylation, methylation, lipidation and their inverse reactions. Among these, SUMOylation and NEDDylation are ubiquitin-like multi-enzymatic processes that determine the bound of SUMOs and NEDD8 labels, respectively, on defined amino acidic residues of a specific protein and regulate protein function. As fate-determinants of several effectors and mediators, SUMOylation and NEDDylation play relevant roles in many aspects of tumor cell biology. Bone represents a preferential site of metastasis for solid tumors (e.g., breast and prostate cancers) and the primary site of primitive tumors (e.g., osteosarcoma, chondrosarcoma). Deregulation of SUMOylation and NEDDylation affects different aspects of neoplastic transformation and evolution such as epithelial-mesenchymal transition, adaptation to hypoxia, expression and action of tumor suppressors and oncogenic mediators, and drug resistance. Thereby, they represent potential therapeutic targets. This narrative review aims at describing the involvement and regulation of SUMOylation and NEDDylation in tumor biology, with a specific focus on primary and secondary bone tumors, and to summarize and highlight their potentiality in diagnostics and therapeutic strategies.